An Evolutionarily Conserved Mechanism for Activity-Dependent Visual Circuit Development - Pratt, Kara G.; Hiramoto, Masaki; Cline, Hollis T. (Frontiers in Neural Circuits, 2016)
Neural circuit development is an activity-dependent process. This activity can be spontaneous, such as the retinal waves that course across the mammalian embryonic retina, or it can be sensory-driven, such as the activation of retinal ganglion cells by visual stimuli. Whichever the source, neural activity provides essential instruction to the developing circuit. Indeed, experimentally altering activity has been shown to impact circuit development and function in many different ways and in many different model systems. In this review we contemplate the idea that retinal waves in amniotes, the animals that develop either in ovo or utero (namely reptiles, birds, mammals) could be an evolutionary adaptation to life on land, and that the anamniotes, animals whose development is entirely external (namely the aquatic amphibians and fish), do not display retinal waves, most likely because they simply don’t need them. We then review what is known about the function of both retinal waves and visual stimuli on their respective downstream targets, and predict that the experience-dependent development of the tadpole visual system is a blueprint of what will be found in future studies of the effects of spontaneous retinal waves on instructing development of retinorecipient targets such as the superior colliculus and the lateral geniculate nucleus.